Stroke Rates Following Surgical Versus Percutaneous Coronary Revascularization - Head, Stuart J; Milojevic, Milan; Daemen, Joost; Ahn, Jung-Min; Boersma, Eric; Christiansen, Evald H; Domanski, Michael J; Farkouh, Michael E; Flather, Marcus; Fuster, Valentin; Hlatky, Mark A; Holm, Niels R; et al. (Journal of the American College of Cardiology, 2018)
Coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) are used for coronary revascularization in patients with multivessel and left main coronary artery disease. Stroke is among the most feared complications of revascularization. Due to its infrequency, studies with large numbers of patients are required to detect differences in stroke rates between CABG and PCI. This study sought to compare rates of stroke after CABG and PCI and the impact of procedural stroke on long-term mortality. We performed a collaborative individual patient-data pooled analysis of 11 randomized clinical trials comparing CABG with PCI using stents; ERACI II (Argentine Randomized Study: Coronary Angioplasty With Stenting Versus Coronary Bypass Surgery in Patients With Multiple Vessel Disease) (n = 450), ARTS (Arterial Revascularization Therapy Study) (n = 1,205), MASS II (Medicine, Angioplasty, or Surgery Study) (n = 408), SoS (Stent or Surgery) trial (n = 988), SYNTAX (Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery) trial (n = 1,800), PRECOMBAT (Bypass Surgery Versus Angioplasty Using Sirolimus-Eluting Stent in Patients With Left Main Coronary Artery Disease) trial (n = 600), FREEDOM (Comparison of Two Treatments for Multivessel Coronary Artery Disease in Individuals With Diabetes) trial (n = 1,900), VA CARDS (Coronary Artery Revascularization in Diabetes) (n = 198), BEST (Bypass Surgery Versus Everolimus-Eluting Stent Implantation for Multivessel Coronary Artery Disease) (n = 880), NOBLE (Percutaneous Coronary Angioplasty Versus Coronary Artery Bypass Grafting in Treatment of Unprotected Left Main Stenosis) trial (n = 1,184), and EXCEL (Evaluation of Xience Versus Coronary Artery Bypass Surgery for Effectiveness of Left Main Revascularization) trial (n = 1,905). The 30-day and 5-year stroke rates were compared between CABG and PCI using a random effects Cox proportional hazards model, stratified by trial. The impact of stroke on 5-year mortality was explored. The analysis included 11,518 patients randomly assigned to PCI (n = 5,753) or CABG (n = 5,765) with a mean follow-up of 3.8 ± 1.4 years during which a total of 293 strokes occurred. At 30 days, the rate of stroke was 0.4% after PCI and 1.1% after CABG (hazard ratio [HR]: 0.33; 95% confidence interval [CI]: 0.20 to 0.53; p < 0.001). At 5-year follow-up, stroke remained significantly lower after PCI than after CABG (2.6% vs. 3.2%; HR: 0.77; 95% CI: 0.61 to 0.97; p = 0.027). Rates of stroke between 31 days and 5 years were comparable: 2.2% after PCI versus 2.1% after CABG (HR: 1.05; 95% CI: 0.80 to 1.38; p = 0.72). No significant interactions between treatment and baseline clinical or angiographic variables for the 5-year rate of stroke were present, except for diabetic patients (PCI: 2.6% vs. CABG: 4.9%) and nondiabetic patients (PCI: 2.6% vs. CABG: 2.4%) (p for interaction = 0.004). Patients who experienced a stroke within 30 days of the procedure had significantly higher 5-year mortality versus those without a stroke, both after PCI (45.7% vs. 11.1%, p < 0.001) and CABG (41.5% vs. 8.9%, p < 0.001). This individual patient-data pooled analysis demonstrates that 5-year stroke rates are significantly lower after PCI compared with CABG, driven by a reduced risk of stroke in the 30-day post-procedural period but a similar risk of stroke between 31 days and 5 years. The greater risk of stroke after CABG compared with PCI was confined to patients with multivessel disease and diabetes. Five-year mortality was markedly higher for patients experiencing a stroke within 30 days after revascularization.